KEABSAHAN PERMEN DALAM TRANSAKSI PEMBAYARAN - Pasek Dwilaksmi, Ni Made Ayu; Ari Yuliartini Griadhi, Ni Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015)
The validity of this scientific work titled Candy In Payment Transactions. Backgroundof this paper is the number of complaints of consumers who experience unpleasant eventsassociated with his change is replaced with candy when doing transactions at thesupermarket. This study aims to determine the validity of candy in payment transactions. Thispaper uses the normative method by analyzing the problems with the law and relevantliterature. The conclusion of this paper is the validity of candy in payment transactions underthe provisions of Article 2 paragraph ( 2 ) of Law Number. 7 of 2011 on Currency and BankIndonesia Regulation Number. 6/14/PBI/2004 , are legal tender coins and money paper, thecandy is not legal tender.
Keywords: Validity , Candy , Transaction , Payments